Challenges in automated estimation of capillary refill time in dogs - Cugmas, Blaž; Spīgulis, Jānis (SPIE, 2018)
Capillary refill time (CRT) is a part of the cardiorespiratory examination in dogs. Changes in CRT can reflect pathological conditions like shock or anemia. Visual CRT estimation has low repeatability; therefore, optical systems for automated estimation have recently appeared. Since existing systems are unsuitable for use in dogs, we designed a simple, small and portable device, which could be easily used at veterinary clinic. The device was preliminarily tested on several measurement sites in two dogs. Not all measurement sites were suitable for CRT measurements due to underlying tissue optical and mechanical properties. The CRT measurements were possible on the labial mucosa, above the sternum and on the digit where CRT was in the range of values, retrieved from the color video of the visual CRT measurement. It seems that light penetration predominantly governs tissue optical response when the pressure is applied. Therefore, it is important to select a proper light, which reaches only superficial capillaries and does not penetrate deeper. Blue or green light is probably suitable for light skin or mucosa, on the other hand, red or near-infrared might be used for skin with pigmented or thick epidermis. Additionally, further improvements of the device design are considered, like adding a calibrated spring, which would insure application of consistent pressure.
Keywords: Capillary refill time, veterinary medicine, dogs, monitoring, pulse oximeter, photoplethysmography; Research Subject Categories::NATURAL SCIENCES::Physics; Research Subject Categories::VETERINARY MEDICINE; Capillary refill time; Dogs; monitoring; pulse oximeter; photoplethysmography